Identification of HPV16 E1 and E2-specific T cells in the oropharyngeal cancer tumor microenvironment - Christine McInnis; Lakshmi Srinivasan; Anthony J Coyle; Shilpa Bhatia; Glenn J Hanna; Ann Marie Egloff; Brinda Vijaykumar; Qiaomu Tian; Yanbo Sun; Del Leistritz-Edwards; Charles T Quinn; Ravi Uppaluri; et al. (Journal for ImmunoTherapy of Cancer)
Background High-risk human papillomavirus (HPV) is a primary cause of an increasing number of oropharyngeal squamous cell carcinomas (OPSCCs). The viral etiology of these cancers provides the opportunity for antigen-directed therapies that are restricted in scope compared with cancers without viral components. However, specific virally-encoded epitopes and their corresponding immune responses are not fully defined.Methods To understand the OPSCC immune landscape, we conducted a comprehensive single-cell analysis of HPV16+ and HPV33+ primary tumors and metastatic lymph nodes. We used single-cell analysis with encoded peptide-human leukocyte antigen (HLA) tetramers to analyze HPV16+ and HPV33+ OPSCC tumors, characterizing the ex vivo cellular responses to HPV-derived antigens presented in major Class I and Class II HLA alleles.Results We identified robust cytotoxic T-cell responses to HPV16 proteins E1 and E2 that were shared across multiple patients, particularly in HLA-A*01:01 and HLA-B*08:01. Responses to E2 were associated with loss of E2 expression in at least one tumor, indicating the functional capacity of these E2-recognizing T cells and many of these interactions validated in a functional assay. Conversely, cellular responses to E6 and E7 were limited in quantity and cytotoxic capacity, and tumor E6 and E7 expression persisted.Conclusions These data highlight antigenicity beyond HPV16 E6 and E7 and nominate candidates for antigen-directed therapies.